Refugee children in the UK. Issue 1 (January 2016) - Hands, Christopher; Thomas, Jessica; John-Legere, Stacy
Abstract: Across the globe, persecution, conflict, and famine drive people from their homes. In 2014 59.5 million people were forcibly displaced, of whom more than half were children. Of those people, 38.2 million had been displaced within their country of nationality, whilst 21.3 million had crossed borders to seek refuge. In the summer of 2015, forced migration gained particular prominence in the world's media, as large numbers of migrants made the journey to Europe, and the member states of the European Union dramatized the complexities of the laws and treaties relating to migration into and within the EU. Each year a proportion of the world's displaced and dispossessed people seek refuge in the UK. For the year ending June 2015, 25, 771 main applicants sought asylum in the UK, and 8% of these (2168) were children seeking asylum alone. The top three countries from which people sought asylum in the UK were Eritrea, Pakistan and Syria. Paediatricians will encounter refugee and asylum seeking children in a variety of situations. This review describes the rights and realities of refugee children, and suggests ways in which paediatricians can support them.